Merseyside Artists. - Walker Art Gallery, Liverpool; Williamson Art Gallery & Museum, Birkenhead; Atkinson Art Gallery, Southport; Grosvenor Museum, Chester; Huyton Central Library; St. Helens Museum & Art Gallery (Liverpool : Merseyside Exhibitions, 1983)
Ashton, Graham ; Bailey, Peter ; Beckett, Colin ; Bent, Richard ; Burgoyne, Lis ; Butler, Anthony ; Campbell, Susan ; Cockrill, Maurice ; Colmer, Richard Clavering ; Drought, George J. ; Fields, Ray ; Forrest, Edwin V. ; Green, Frank ; Henri, Adrian ; etc.
Merseyside Artists, Walker Art Gallery, Liverpool, April 25 - May 22 1983 / Williamson Art Gallery & Museum, Birkenhead, July 30 - August 28, 1983 / Atkinson Art Gallery, Southport, September 17 - October 15, 1983 / Grosvenor Museum, Chester, October 29 - December 11, 1983 / Huyton Central Library, January 18 - February 22, 1984 / St. Helens Museum & Art Gallery, March 6 - APril 3, 1984
boek